2007
DOI: 10.1524/ract.2007.95.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Uranium(VI) complexation by humic acid under neutral pH conditions studied by laser-induced fluorescence spectroscopy

Abstract: The complexation of U(VI) with Aldrich humic acid (HA) was studied at pH 7 under exclusion of CO 2 . Using two independent laser-induced spectroscopic methods, timeresolved laser-induced fluorescence spectroscopy (TRLFS) and TRLFS with ultrafast pulses (fs-TRLFS), the formation of the ternary U(VI) mono hydroxo humate complex UO 2 (OH)HA(I) by reaction of UO 2 OH + with HA was studied. Assuming that all proton exchanging functional groups of the HA are able to contribute to the complex formation, a mean stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 31 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…In addition, at the pH around 7, such as measured in our study, Sachs et al (2007) reported significant formation of uranium complexes with humic substances, which are abundant organic ligands of natural origin, and made up approximately 60% of the carbon dissolved in aquatic systems (Peña-Méndez et al 2005). As a consequence of the increased use of fertilizers in the modern agriculture, additional input of humic substances into the river water can occur due to their use as additives to fertilizers (Peña-Méndez et al 2005), which could resulted in uranium complexation and further concentration increase in the river water at agriculturally impacted downstream sites.…”
Section: Diffuse Source Water Contaminationsupporting
confidence: 63%
“…In addition, at the pH around 7, such as measured in our study, Sachs et al (2007) reported significant formation of uranium complexes with humic substances, which are abundant organic ligands of natural origin, and made up approximately 60% of the carbon dissolved in aquatic systems (Peña-Méndez et al 2005). As a consequence of the increased use of fertilizers in the modern agriculture, additional input of humic substances into the river water can occur due to their use as additives to fertilizers (Peña-Méndez et al 2005), which could resulted in uranium complexation and further concentration increase in the river water at agriculturally impacted downstream sites.…”
Section: Diffuse Source Water Contaminationsupporting
confidence: 63%
“…TRLFS measurements [11] showed that, even if HA is present, U(VI) prefers to sorb directly onto kaolinite rather than via HA. Aqueous U(VI)-humate complexes themselves do not show any fluorescence at all under the applied measuring conditions [12]. So, if U(VI) would be bound to kaolinite by HA, no fluorescence of U(VI) in the U(VI)-HA-kaolinite samples should be observed.…”
Section: Introductionmentioning
confidence: 90%
“…Using the log * β • n in [47] for hydrolysis and log * β 1.4.I = −3.8 for U(OH) 4 HA(I), and other constants in Table 3 for UO 2 + , using analogy with NpO 2 + [56], and UO 2 2+ [11,78], speciation calculations can be done under the conditions given in [31, Table 1] for SCWHA and SCWHA/C.…”
Section: Uranium(iv) Laboratory Datamentioning
confidence: 99%